Failure of pedicled flap reconstruction in the head and neck area: A case report of a bilateral subclavian artery stenosis. (2020) - Sievert, Matti; Koch, Michael; Mantsopoulos, Konstantinos; Traxdorf, Maximilian; Mueller, Sarina K.; Iro, Heinrich; Scherl, Claudia
Highlights: Pedicled flap reconstruction in the head and neck is still an alternative if free flaps are not possible. Angiography of the subclavian artery is not a standard procedure in the surgical planning of pedicle flap harvesting. In exceptional cases, we recommend angiography of the neck and thoracic vessels. The application of a temporary pharyngostoma is still an option in extraordinary circumstances. Abstract: Introduction: Pedicled flap reconstruction still plays an essential role in head and neck surgery as an alternative to free grafts. Two standard methods are the pectoralis major and the deltopectoral flap, which are generally characterized by their reliable perfusion. This case describes bilateral arteriosclerosis of the subclavian artery as a possible cause of flap failure. Presentation of case: We report on a 65-year-old patient with a multilevel carcinoma of the right pharynx. Due to the unique patient history, a free flap reconstruction was not possible. After resection of the primary, we performed reconstruction with a pedicled pectoralis major flap. Discussion: Postoperatively, we observed necrosis of the pectoralis major flap. Secondary defect reconstructions were performed with a deltopectoral flap first from the right and then, in the case of necrosis, from the left side. Stenosing arteriosclerotic plaques of the subclavian artery on both sides were the cause of flap failure. Conclusion: Preoperative angiography of the subclavian artery is not a standard diagnostic procedure in the surgical planning of pedicled flap reconstruction in the head and neck region. In exceptional cases, we recommend angiographic imaging of the supplying vessels to make a more precise flap selection and avoid complications.